Upaya Peningkatan Potensi Pendapatan Asli Daerah Melalui Intensifikasi Pajak Kendaraan Bermotor (Studi Pada Penerapan Skema Opsen Pajak Kendaraan Bermotor Wilayah Surabaya Timur) - Romadhona, Aisyah Faradilla; Ma’ruf, Muhammad Farid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Law Number 1 of 2022 concerning Financial Relations Between the Central Government and Regional Governments, becomes a law that regulates fiscal authority in regions in managing Motor Vehicle Tax revenues. Through the implementation of the Motor Vehicle Tax opsen scheme as a form of tax intensification in an effort to increase the potential for Regional Original Income. This study aims to analyze and determine how the implementation of tax intensification in increasing the potential for Regional Original Income through the implementation of the opsen scheme in collecting Motor Vehicle Tax in the East Surabaya Region. This study uses a descriptive qualitative research method. The findings in this study indicate that there are efforts to increase the potential for Regional Original Income revenues through tax intensification by the East Surabaya Regional Revenue Management Technical Implementation Unit which has the authority to manage the implementation of the Motor Vehicle Tax opsen scheme in the East Surabaya Region.